Essential Oil Composition of Green Peel of the Inter-Varietal Mandarin Hybrid, Kinnow Orange (Biological Sciences - PJSIR, 2005)
The essential oil of green peel of large-sized Kinnow fruits was obtained by steam distillation, which recorded a yield of 0.34%. Kinow is a hybrid of inter-varietal cross of the mendarin orange cultivars, King x Mediterranean. The oil was analyzed by GC and MS procedures. Among a variety of the oil constituents, 24 compounds were identified by GC, which were further analyzed for their chemical nature through GC-MS. The major proportion of the indentified constituents comprised of 6-methyl-5-heptene-2-one (15.33%), carvone (13.8%), cis-carveol (10.04%) and thujanol (4.55%). Rest of the twenty identified compounds occurred in minor amounts, comprised of 35.84% of the total oil. Limonene, usually the major component of the citrus oils (35-85%), was present in rather low quantities (2.76%) in the Kinnow orange green peel oil.